NATIONAL ACTION GAMES AND PRACTICAL SIGNIFICANCE OF THEIR DEVELOPMENT - Xaqnazarov Qurbon Qoshayevich (American Journals, 2023)
The importance of national games. Organization of national action games Distinctive aspects of transfer. The importance of national games. Thanks to the independence, wide prospects are opening up in the field of physical education and sports, which is especially evident in the physical education classes canceled on the national holidays and exercises of the people, sports. Keeping them constant and regular gives good results, serves as an important factor in raising students to be healthy, energetic, agile and strong. In the past, Navroz holidays, fairs, and weddings, which were attended by a large number of people, were not canceled without folk festivals, physical exercises, and national sports.
Keywords: national, future, physical education, since, festival, wedding, developed, negative aspect